If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ab + -1c = 4 Solving bA + -1c = 4 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add 'c' to each side of the equation. bA + -1c + c = 4 + c Combine like terms: -1c + c = 0 bA + 0 = 4 + c bA = 4 + c Divide each side by 'A'. b = 4A-1 + cA-1 Simplifying b = 4A-1 + cA-1
| 3z^2-14z=5 | | S=2LH+2LW | | 4q^2-12q=0 | | 9kx^2+2kx+3=0 | | 2k^2-17k=9 | | 2k^2-17k=0 | | ab=21 | | 7a=24 | | X^2-9=3x-1 | | 4/11=20x/33 | | X=8+-1x | | v=3/5=1/4 | | (2x-7)/(9x-5) | | 2x-7/9x-5 | | 4t^2-11t=3 | | 228=-19p | | 3+2x+1+3+2x+1=16 | | V-4/3=5/4 | | 19.1=13.1-n | | 4x^3=(x/3) | | 12x-4+6x+3=10 | | (w/2)-3h=53 | | 4.36=4/3(3.14)r^3 | | p-5/8=19/8 | | 6[4*(72-63)/3] | | 21(2+x)12x=44 | | X-x+5x-3=3x+5 | | 0.20(y-3)+0.02y=0.06y-1.4 | | (3/10)x-2=(1/5)x | | -1/11-2/11 | | V/2-4=-12 | | (-2)(3)(-3)(-2)= |